Special supplement 1977 británica book of the year / Charles Van Doren - Doren, Charles Van (1977)
The aftermath of Angola, an appraisal of the sudden turn of events in southern Africa, by basil Davidson; the coming of medicated man, a personal view of the metric system, by Herbert Greenberg; Mexican mythology and modern society, the influence of the mythical plumed serpent is enduring, by José López portillo.